7Be, 210Pb and 40K depositions over 11 years in Málaga. (November 2017) - Dueñas, C.; Gordo, E.; Liger, E.; Cabello, M.; Cañete, S.; Pérez, M.; Torre-Luque, P. de la
Abstract: The monthly bulk depositional fluxes of three natural radionuclides ( 7 Be, 210 Pb and 40 K) were measured at a Mediterranean coastal station (Málaga) over an 11-year period from 2005 to 2015. The mean annual depositional fluxes of 7 Be, 210 Pb and 40 K were 1215, 144 and 67 Bq m −2 year −1 respectively, showing a clear seasonal trend with minimum values recorded during summer and maximum values in winter. The rainfall regime with dry summers allows estimating the dry deposition. Assuming constant dry deposition through each year, 7 Be, 210 Pb and 40 K would account for 12.5, 26.5 and 33% of the bulk fallout respectively which indicates that deposition for 210 Pb and 40 K are significantly higher than 7 Be. The precipitation-normalized enrichment factor alpha used to explain seasonal variations in the depositional fluxes of radionuclides with respect the rainfall, indicates higher depositional fluxes during spring and summer than expected from the amount of rainfall. Despite their different origin, 210 Pb and 7 Be monthly depositional fluxes have strong correlation. The atmospheric deposition fluxes of 7 Be, 210 Pb and 40 K were controlled mainly by the amount of rainfall (r = 0.89, 0.91 and 0.66 respectively). Moreover, principal component analysis was applied to the datasets and deposition of radionuclides and rainfall in the same component highlighting the importance of the washout mechanism. The mean depositional velocity of aerosols evaluated using 7 Be and 210 Pb are similar and are compared to other published values. Highlights: Longest period for the depositional flux study of 7 Be and 210 Pb in Mediterranean area. Statistical analyses: correlations and principal component analysis are performed. Relationship among atmospheric deposition of natural radionuclides and some variables. Influence of rainfall (amount and duration) on fluxes of radionuclides is highlighted. Evaluation of the dry fallout deposition of 7 Be and 210 Pb.